Role of the tomato fruit ripening regulator MADS-RIN in resistance to Botrytis cinerea infection. (15th October 2021) - Zheng, Hui; Jin, Rong; Liu, Zimeng; Sun, Cui; Shi, Yanna; Grierson, Donald; Zhu, Changqing; Li, Shan; Ferguson, Ian; Chen, Kunsong
Abstract: Tomato MADS-RIN (RIN) transcription factor has been shown to be a master activator regulating fruit ripening. Recent studies have revealed that in addition to activating many other cell wall genes, it also represses expression of XTH5, XTH8, and MAN4a, which are positively related to excess flesh softening and cell wall degradation, which might indicate it has a potential role in pathogen resistance of ripening fruit. In this study, both wild-type (WT) and RIN-knockout ( RIN-KO ) mutant tomato fruit were infected with Botrytis cinerea to investigate the function of RIN in defense against pathogen infection during ripening. The results showed that RIN-KO fruit were much more sensitive to B. cinerea infection with larger lesion sizes. Transcriptome data and qRT-PCR assay indicate genes of phenylalanine ammonialyase ( PAL ) and chitinase ( CHI ) in RIN-KO fruit were reduced and their corresponding enzyme activities were decreased. Transcripts of genes encoding pathogenesis-related proteins ( PRs ), including PR1a, PRSTH2, and APETALA2/Ethylene Response Factor ( AP2/ERF ) including ERF.A1, Pti5, Pti6, ERF.A4, were reduced in RIN-KO fruit compared to WT fruit. Moreover, in the absence of RIN the expression of genes encoding cell wall-modifying enzymes XTH5, XTH8, MAN4a has been reported to be elevated, which is potentially correlated with cell wall properties. When present, RIN represses transcription of XTH5 by activating ERF.F4, a class II (repressor class) ERF gene family member, and ERF.F5. These results support the conclusion that RIN enhances ripening-related resistance to gray mold infection by upregulating pathogen-resistance genes and defense enzyme activities as well as reducing accumulation of transcripts encoding some cell wall enzymes.